Polarimetry of an intermediate-age open cluster: NGC 5617 - Orsatti, Ana María (2010)
Aims. We present polarimetric observations in the UBVRI bands of 72 stars located in the direction of the medium age open cluster NGC 5617. Our intention is to use polarimetry as a tool in membership identification, by building on previous investigations intended mainly to determine the cluster's general characteristics rather than provide membership suitable for studies such as stellar content and metallicity, as well as study the characteristics of the dust lying between the Sun and the cluster. Methods. The obsevations were carried out using the five-channel photopolarimeter of the Torino Astronomical Observatory attached to the 2.15 m telescope at the Complejo Astronómico El Leoncito (CASLEO; Argentina). Results. We are able to add 32 stars to the list of members of NGC 5617, and review the situation for others listed in the literature. In particular, we find that five blue straggler stars in the region of the cluster are located behind the same dust as the member stars are and we confirm the membership of two red giants. The proposed polarimetric memberships are compared with those derived by photometric and kinematical methods, with excellent results. Among the observed stars, we identify 10 with intrinsic polarization in their light. NGC 5617 can be polarimetrically characterized with Pmax = 4.40 % and θv = 73°1. The spread in polarization values for the stars observed in the direction of the cluster seems to be caused by the uneven distribution of dust in front of the cluster's face. Finally, we find that in the direction of the cluster, the interstellar medium is apparently free of dust, from the Sun's position up to the Carina-Sagittarius arm, where NGC 5617 seems to be located at its farthest border.